Religious Soundscape, Sacred Space, and Affective Body: The Experience of Sufi Whirling Ritual Practitioners in Java - Nurwendah, Yusti Dwi; Kailani, Najib; Udasmoro, Wening (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
This article explores the experience of cultivating religious senses and sensibilities through ritual Sufi dance. In contemporary Indonesia, Sufi dance serves both as a performance and a ritual. As a performance, it is staged at specific events; as a ritual, it acts as a religious practice, engaging the body and fostering a connection with God to experience spiritual ecstasy. Employing a phenomenological approach, the research data were gathered through interviews, participant observation, and social media. This article focuses on the Tari Sufi Mafia Sholawat group, the predominant Sufi dance community in Java, and illustrates how sound and listening during Sufi dance rituals significantly nurture and enhance religious sensibility and the affective body. Furthermore, it identifies various sounds present in the Sufi dance performance that resonate with listeners’ senses and sensibilities. These sounds evoke a range of bodily actions and emotional responses from the performers, such as hand movements, closed eyes, weeping, and screaming. The dancers perform these movements within a sacred space, thereby amplifying their spiritual impact.